The irrelevance of case for DP movement in English - Newson, Mark (LingBaW. Linguistics Beyond and Within, 2024)
A particular view of English case assignment falls out from an assumption within Dependent Case theory that there are only two structural cases: dependent and unmarked. The different forms of DPs do not necessarily indicate different assigned cases, but may be different contextually determined exponents of the same case. From this perspective, it can be argued that English has a neutral case system. Pronouns have contextually determined forms realising one underlying case. As a consequence, standard assumptions about the interaction of case assignment and movement can be questioned. Many assumptions concerning the exceptional status of certain constructions can be dropped in favour of a simpler theory in which case is assigned to DPs in their base positions.